2009
DOI: 10.2166/wh.2009.038
|View full text |Cite
|
Sign up to set email alerts
|

Water consumption habits of a south-western Ontario community

Abstract: A cross-sectional telephone survey (n ¼ 2,332) was performed to better understand the drinking water consumption patterns among residents in Waterloo Region, Ontario, Canada. We investigated the daily volume of water consumed (including tap and bottled) and factors related to that consumption. In addition, we investigated the daily volume of cold tap water consumed by those respondents who consumed no bottled water and the factors that influence this consumption. Among study respondents, 51% exclusively drank … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
22
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 21 publications
5
22
0
Order By: Relevance
“…The other possible sources of positive consumer perceptions of bottled water could involve the variety of the brands, sizes, sources, types, and flavor; however, there is very little scientific proof to support the belief that bottled water is better quality than tap water (Napier & Kodner, 2008). In Canada, a survey of a southwestern Ontario community revealed that 37% of the residents drink bottled water as their only drinking water source due to their discomfort with the tap water flavor (Pintar et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The other possible sources of positive consumer perceptions of bottled water could involve the variety of the brands, sizes, sources, types, and flavor; however, there is very little scientific proof to support the belief that bottled water is better quality than tap water (Napier & Kodner, 2008). In Canada, a survey of a southwestern Ontario community revealed that 37% of the residents drink bottled water as their only drinking water source due to their discomfort with the tap water flavor (Pintar et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Since then, several studies have examined water consumption patterns of Canadian residents, but many were restricted to specific geographic locations (e.g. Craun & Calderón 2006;Jones et al 2006aJones et al , b, 2007bPintar et al 2009). Recently, however, new research investigating drinking water consumption patterns and determinants for an individual's choice has been published, highlighting the importance of nationally representative data (Dupont et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In the past nine years, seven cross-sectional, communifylevel surveys with drinking water assessment components were performed within specific regions of Ontario (Jones et al 2006a, b, unpublished;Pintar et al 2009), British Columbia (Jones et al 2007b), and Newfoundland and Labrador (Butt 2010;Roche & Jones unpublished). The overall purpose of the present study was to pool the data from the seven studies in order to estimate Canadian drinking water consumption patterns.…”
Section: Introductionmentioning
confidence: 99%
“…Concerns regarding tap water quality could be attributed to demographic variations including race, age, income, occupation and gender (FWR, 1996;Abrahams et al, 2000;Dupont et al, 2010). Also, the perceived quality of the water source can be a significant predictor of bottled water consumption (Levallois et al, 1999;Anadu and Harding, 2000;Pintar et al, 2009;Hu et al, 2011). Other factors that influence public behavior are past incidents of tap water contamination, trust in tap water companies, marketing of bottled water companies (Giacosa and Giovando, 2012), changes of life style, increasing standards of living, the wide spread markets of bottled water (Ferrier, 2001), among others.…”
Section: Introductionmentioning
confidence: 99%